Source of Stable Single-Phase Voltage to 60V, Current to 6A and Adjustable Angle between Voltage and Current from 0 to 360° - Žigić, Aleksandar D; Milosavljević, Srđan; Lukić, Ivan; Škundrić, Slobodan; Bolić, Dušan; Cakić, Nikola N. (Proceedings, Electrical engineering institute "Nikola Tesla", 2013)
This paper describes a realized AC voltage power supply source of 50Hz with two outputs: voltage to 60V and current to 6A, with maximum generated power of both of 10VA. A short technical description of the realized device with a structural and functional block diagram is given. The main technical characteristics, working principles and application possibilities of the device are specified. The results of the investigations on the realized device are included.